The development and implementation of a mental toughness training programme for cricketers - McInerney, Michael (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
The professional turn in sports has prompted the search for explanations beyond the physical when discussing quality of performance. Mental Toughness has been recognised as one of the most important psychological attributes in achieving performance excellence across multiple sport settings. Yet, despite this, little research has been conducted into mental toughness development. This research seeks to answer the question: What insights can the development and implementation of a mental toughness programme for a semi-professional South African cricket team provide regarding Mental Toughness development? Based on a theoretical framework of mental toughness in cricket, a programme was developed in collaboration with the Border Cricket Team and Coaches. Incorporating elements that focussed on education, environment, awareness and mental skills, the programme was implemented in both individual and group settings during the off- and pre-seasons. An analysis of the participants' experiences identified the need for a theoretical understanding of mental toughness within teams, facilitating the design of interventions that integrate the team and the individual. Future programmes should include measures of mastery, and individually customised approaches to mental toughness enhancement that acknowledge the potential contextual and individual variation in mental toughness.
Keywords: Sports -- Psychological aspects; Athletes -- Conduct of life; Mental discipline; Achievement motivation